Evaluación de la aplicación de fibra óptica en un completamiento inteligente para drenaje gravitacional asistido por vapor SAGD que permita el control de temperatura en fondo de pozo (2023)
Worldwide, new enhanced recovery techniques are being sought to implement them in heavy crude oil deposits, since most of the world's reserves are of this type of hydrocarbon. A currently existing recovery method is steam-assisted gravity drainage, SAGD, which has been implemented in bitumen deposits, where successful results have been achieved, obtaining recovery factors greater than 50%. The technique consists of two horizontal wells, one located a few feet above the other, depending on the viscosity of the hydrocarbon, in which continuous steam injection is made through the upper well where, due to differences in densities, the steam tends to expand to the top. of the formation and the heated hydrocarbons together with the water vapor that is condensed and drains towards the lower well, which is the producing well. The mechanism of production of gravitational segregation, which is used for this type of reservoirs with very viscous crudes, can flow from being heated this hydrocarbon towards the producing well due to the effect of gravity, for which it is necessary that there is connectivity between the two wells.